The Universality Of Mutual Respect And Humility In The Al-quran: Towards The Construction Of A Value-based Arabic Grammar - Muhammad Zahid Ismail; Mohd Nizwan Musling; Mohd Rosmizi Abd Rahman (Human Resource Management Academic Research Society, 2024)
Indexed by ERA